SOME ASPECTS OF THE BIOLOGY OF OTOLITHES CUVIERI (TREWA VAS) AND JOHNIUS GLAUCUS (DAY) FROMVERAV AL - RAJE, SADASHIV GOPAL (Journal of Indian Fisheries Association, 2015)
The length-weight relationship in O.cuvieri and J.glaucus can be described by the equations log W = -5.27997 + 3.13225 log L and log W = -4.93431 + 3.02556 logL respectively. The length at first maturity in O.cuvieri is estimated as 256 mm and in J.glaucus as 180 mm. Empty stomachs occurred in high percentage in both the species. A study on composition of food items revealed that O.cuvieri feeds on a variety of organisms while J. glaucus a selective feeder. Key words : Length-weight relationship, food & feeding, maturation, spawning.